HARD/SOFTWARE FUNCTIONAL CONTROL METHOD OF MICRODISPLAY MODULES FOR PERSONAL VIDEO-PROJECTION SYSTEMS - А. S. Монаммеd; E. V. Mukha; A. A. Stsiapanau; A. V. Pasynkov; A. G. Smirnov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The hard- and software functional control method of microdisplay modules for personal videoprojection systems is presented. The basic components comprise of an active matrix SVGA LCOS microdisplay or a LED microdisplay based on Schottky diodes nanoporous silicon- nanostructured aluminium, a Video Pattern Generator VPG 170 which generates test images with different parameters and characteristics. It’s included also the specialized optical system containing a polarizing cube with antiglare coatings and RGB backlit system. The control of the generator test signals is accomplished using a specially developed software installed in a PC using Windows XP operating system.